Manajemen Uji Kompetensi Keahlian Praktik KejuruanSemester Gasal Kelas XII TKR SMK Negeri 2 WonogiriTahun Pelajaran 2016/2017 - Sulistyono, Agung, Dr. Maryadi, M.A, Dr. Achmad Fathoni, M.Pd (2017)
Management of competence test vocational practice skill first semester grade XII TKR SMK Negeri 2 Wonogiri Academic Years 2016/2017. Thesis. Postgraduate. University of Muhammadiyah Surakarta. 2017. This research aims to describe : (1) Planning of test competence material vocational practice skill first semester grade XII TKR SMK Negeri 2 Wonogiri Academic Years 2016/2017. (2) Organizing of productive teachers and assesors of competence test vocational practice skill first semester grade XII TKR SMK Negeri 2 Wonogiri. (3) Implementation of competence test vocational practice skill first semester grade XII TKR SMK Negeri 2 Wonogiri. (4) Evaluating implementation of competence test vocational practice skill first semester grade XII TKR SMK Negeri 2 Wonogiri Academic Years 2016/2017. The research methode covers: qualitative research type with ethnography approach, data collecting technique with documentation, observation and interview deeply, data analysis technique based on data collecting in which the researcher reduces data and data supply in the form of note form the research place which consists of its description and reflection part. The research results cover : (1) Planning of test competence material vocational practice skill first semester grade XII TKR sylabus and lesson plan made and develoded by every teacher in accordance with subject characteristics considering integrated learning experience so that they can meet the basic ability and change student attitude as learning experience. (2) Organizing productive teachers and assesors of competence test in which they should have experience and master in subject materials includes knowledge, skill and attitude aspect as well as having at least five year experience and skill competence test certificate. (3) Implementation of test competence is adapted not only by the basic competence materials but also the readiness of student, equipment, material and problem sheet. (4) Evaluation of skill competence test is a part of curriculum evaluation that is used to review the availability, understanding and benefit of administration document skill competence test TKR. Key Words : Learning management, Skill competence test, vocational practice, light vehicle technique